Social Gamification in Team Sports - Design Concept and Preliminary Evaluation - Birnstiel, Sandra (Workshopband, 2024)
Gamification, the use of game design elements to increase user engagement and motivation in any activity, has evolved in several areas, including sports. However, while the use of gamification in individual sports and fitness contexts has been extensively studied, the potential of gamification in team sports remains poorly explored. This paper addresses this gap by designing and evaluating social gamification features tailored to support team unity in sports teams. Therefore, a gamification concept was designed, consisting primarily of a virtual team mascot that can be unlocked and enhanced by completing team-based performance challenges, aimed at supporting the social relationship within the team. Subsequently, a within-subjects field experiment was conducted with an amateur women's soccer team over a four-week period to assess whether the presented features would increase social identification within the team. The preliminary evaluation revealed that although team members' participation in the given team challenges was moderate, there was a significant increase in social identity, confirming the hypothesis. This study extends the understanding of gamification in team sports, provides preliminary empirical evidence on the effectiveness of social gamification features in this context, and identifies avenues for future research on social gamification in team sports.<br